The Moral Property of Women : A History of Birth Control Politics in America - Gordon, Linda (Book collections on Project MUSE., 2002)
"The only book to cover the entire history of birth control and the intense controversies about reproduction rights that have raged in the United States for more than 150 years, The Moral Property of Women is a thoroughly updated and revised edition of the award-winning historian Linda Gordon's classic history Woman's Body, Woman's Rights, originally published in 1976"--Provided by publisher.